Pelayanan Administrasi Digital untuk Meningkatkan Kinerja Pelayanan Administrasi di Desa Kalisidi - Rini Muzayanah; Muhammad Syauqi Al-Haqqi; Subhan Subhan; Apri Dwi Lestari; Muhammad Daffa Izzuddin; Yuliana Putri Setyowati; Fidya Nur Styaningsih; Nur Afan Syarifudin; Ahmad Raihan; Wiyan Herra Herviana; Adam Satrio Kanza; Muhammad Iqhbal Abdillah; Istiqomah Istiqomah; Rafael Vito Adrian; Gading Nur Salmi; Cecep Bagus Surya Karta Atmaja; Budi Prasetio (IKIP PGRI Bojonegoro, 2023)
ABSTRACTVillage is the smallest element in the goverment administration which has an obligation to realize the welfare of the village community. To create the welfare of the community, administrative services must be carried out effectively by implementing digitalization. This activity will identify training activities on digitizing administrative services carried out in Kalisidi Village and analyze the extent of the influence of digitalization on improving village government performance. The methods that the researcher uses in writing this article include Forum Group Discussion (FGD), demonstration, and evaluation. The surveys carried out included an analysis of service needs in Kalisidi village, demonstration of the use of services, and observation of satisfaction with the service system of Kalisidi Village that had been developed. The results of the training activities carried out can be seen from the understanding of the skateholder of Kalisidi village in using the Kalisidi village information management service system. The existence of training on digitizing administrative services should maximize the use of digital service information systems so that the performance of the Kalisidi village government increases.. Kata Kunci: Digitalization; Administration; Village;Training. ABSTRAKDesa merupakan unsur terkecil dalam tata kelola pemerintahan yang memiliki kewajiban untuk menciptakan kesejahteraan masyarakat desa. Untuk menciptakan kesejahteraan masyarakat, tata kelola pelayanan administrasi harus dilakukan secara efektif dengan mengimplementasikan Digitalisasi. Kegiatan ini akan mengidentifikasi kegiatan pelatihan digitalisasi pelayanan administrasi yang dilaksanakan di Desa Kalisidi untuk mengetahui sejauh mana pengaruh digitalisasi terhadap peningkatan kinerja pemerintahan desa dalam kegiatan pelayanan administrasi. Metode yang peneliti gunakan dalam penulisan artikel ini antara lain Forum Group Discussion (FGD), demonstrasi, dan evaluasi. Survei yang dilakukan meliputi analisis kebutuhan layanan di desa Kalisidi, demonstrasi penggunaan layanan, dan observasi kepuasan terhadap sistem pelayanan Desa Kalisidi yang telah dikembangkan. Hasil dari kegiatan pelatihan yang dilakukan dapat dilihat dari pemahaman perangkat desa Kalisidi dalam menggunakan sistem layanan manajemen informasi desa kalisidi. Adanya pelatihan digitalisasi pelayanan administrasi hendaknya memaksimalkan penggunaan sistem informasi pelayanan digital agar kinerja pemerintah desa Kalisidi meningkat. Kata Kunci: Digitalisasi; Administration; Desa; Pelatihan.